Nature and human relationship in Tintern Abbey - Acharya, Dhiraj (Medha: A Multidisciplinary Journal, 2025)
This research deals about the Nature and human connection in “Tintern Abbey” shows the ecological theme. For the analysis of this paper nature and human connection, glorification of nature and ecological cycle have been presented as research questions. It reflects about the importance of nature for the living of human beings. This research is based on library work. It is applied on the qualitative methodology and explanatory method. Human beings and nature are interconnected to each other and there are threats for the human and nature connection. It shows the human memory is affected by nature. Ecological disasters caused by human beings cause ecological imbalance. For ecological balance in the environment it is necessary to maintain harmony between ecology and human beings. Human and ecological harmony leads to the mental growth of human beings. There is good bonding between human and nature. Nature is the source for food, happiness and peace for human beings. It tracks environmental ideas in connections to human beings. Nature and human are interconnected to one other.